2019
DOI: 10.1007/s10459-019-09925-1
|View full text |Cite
|
Sign up to set email alerts
|

Opening the black box of selection

Abstract: Medical school selection is currently in the paradoxical situation in which selection tools may predict study outcomes, but which constructs are actually doing the predicting is unknown (the 'black box of selection'). Therefore, our research focused on those constructs, answering the question: do the internal structures of the tests in an outcomebased selection procedure reflect the content that was intended to be measured? Downing's validity framework was applied to organize evidence for construct validity, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…After estimating costs (e.g. administrative, academic and IT time, software licences, equipment, refreshments for assessors, etc), we will be able to compare groups on outcome measures, such as examination performance, to examine what was spent in relation to the value that was returned (Schreurs et al 2018(Schreurs et al , 2019. This kind of cost-benefit analysis can inform decisions as to the optimal use of resources when planning selection in the future.…”
Section: Discussionmentioning
confidence: 99%
“…After estimating costs (e.g. administrative, academic and IT time, software licences, equipment, refreshments for assessors, etc), we will be able to compare groups on outcome measures, such as examination performance, to examine what was spent in relation to the value that was returned (Schreurs et al 2018(Schreurs et al , 2019. This kind of cost-benefit analysis can inform decisions as to the optimal use of resources when planning selection in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research indicates that the admissions procedure is robust and replicable. 4 , 30 In another study, 30 we compared the constructs we intended to measure (i.e., the derived competencies) with the applicants’ results and found that the constructs we intended to measured were indeed the ones we measured. For more information on the specific selection procedure employed in the current study or on its development, content, and psychometric properties, please see our previous studies.…”
Section: Methodsmentioning
confidence: 93%
“…For more information on the specific selection procedure employed in the current study or on its development, content, and psychometric properties, please see our previous studies. 4 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…This property makes cognitive diagnosis modelling a feasible alternative approach that can encompass the multidimensionality known to exist within items, something intrinsic to certain well-known assessment tools, such as the situational judgement test (Garcia et al, 2014 ). The first instance of a peer-reviewed study using the cognitive diagnostic modelling approach in healthcare professions education was recently published in this journal (Schreurs et al, 2020 ). The authors looked for validity evidence based on the internal structure and response processes of two situational judgement tests used to select undergraduate medical students.…”
Section: Introducing Cognitive Diagnostic Modellingmentioning
confidence: 99%
“…Two parameters are common to both the DINA and G-DINA models: the guessing parameter and the slipping parameter. Whereas the guessing parameter is a false-positive indicator, i.e., the probability of success when the examinee does not have the attributes, the slipping parameter can be seen as a false-negative indicator, i.e., the probability of failure when the examinee has the attributes (de la Torre & Minchen, 2014 ; Schreurs et al, 2020 ).…”
Section: Introducing Cognitive Diagnostic Modellingmentioning
confidence: 99%